Joan Oliver i Salvador Espriu en el teatre de postguerra - Gibert, Miquel Maria (Caplletra. Revista Internacional de Filologia, 2015)
The author sets out the dramatic production of Joan Oliver and Salvador Espriu, two different ways of understanding the concept of theatrical literary creation and of interpreting projection requirements. Oliver, in general, presents the angle of the bourgeois comedy; the critical tone of the drama he produced before the Civil War either disappears or is considerably tempered. Espriu applies himself to a theatre with tragic roots, embellished with the combination of diverse elements, without taking the possibilities of immediate premiere performances into consideration.